Clinical significance of determining individual intraocular pressure in patients with primary open-angle glaucoma in ophthalmological practice - S.V. Balalin; V.P. Fokin; O.V. Yuferov; S.Z. Boskhomdzhieva (РМЖ "Клиническая офтальмология")
S.V. Balalin1, V.P. Fokin1, O.V. Yuferov1, S.Z. Boskhomdzhieva2 1 S. Fyodorov Eye Microsurgery Federal State Institution, Volgograd branch, Volgograd,   Russian Federation 2 Zhemchuev Republican Clinical Hospital, Elista, Russian Federation Aim: to determine tolerant IOP in patients with primary open-angle glaucoma (POAG) and to evaluate the effectiveness of drug therapy for glaucoma. Patients and Methods: tolerant IOP was determined using software and the effectiveness of drug treatment was analyzed in 341 patients with primary open-angle glaucoma (498 eyes). The average age of the patients was 69.5±0.39 years. Patients were divided into groups according to the level of IOP (P0, mm Hg), which was measured against the background of the initial drug therapy: with normal values of ophthalmotonous (fr om 11 to 21 mm Hg) — 69.7% (347 eyes), with moderately increased IOP values (fr om 22 to 32 mm Hg) — 26.5% (132 eyes) and high IOP values (over 32 mm Hg) — 3.8% (19 eyes). Prognosis of the progression rate of the glaucomatous process was estimated by the intolerance index (Iint). Results: the mean value of true IOP against the background of the initial drug therapy was 19.5±0.3 mm Hg, and the mean value of the tolerant pressure was 16.3±0.05 mm Hg, the difference between them was statistically significant (t=10.7; p=0.001). The mean value of the intolerance index was 3.1±0.27 mm Hg. Prognosis of the progression rate of glaucoma was detected in 164 eyes (32.9%), wh ere the intolerance index exceeded 4.7 mm Hg. Slow progression of the disease was found in 154 eyes (30.9%), wh ere the intolerance index ranged from 0.5 mm Hg to 4.7 mm Hg. Prognosis of stabilization of the glaucomatous process was determined in 180 eyes (36.1%). Conclusions: software application for the tolerant IOP determination in 36.9% of cases allowed to identify those needed to strengthen antihypertensive treatment among patients with POAG with normal ophthalmotonus values on the background of drug therapy and in 35,9% of cases to select patients for surgical treatment of glaucoma. Key words: open-angle glaucoma, individual and tolerant intraocular pressure, evaluation of the effectiveness of antihypertensive treatment. For citation: Balalin S.V., FokinV.P. , Yuferov O.V., Boskhomdzhieva S.Z. Clinical significance of determining individual intraocular pressure in patients with primary open-angle glaucoma in ophthalmological practice. RMJ “Clinical ophthalmology”. 2018;4:199–202.